High Frequency Transformer for Ship Electrical Power System - AnuPriya K R; Sasilatha T (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
The system represented during this paper uses 3 matrix converters and a high frequency electrical device to attain isolation and voltage transformation from primary to secondary aspect. Two matrix converters manufacture high frequency voltage across a transformer, with open all over primary. a 3rd matrix device converts the high frequency cut voltage to line frequency. The non-idealities like outflow inductance of the electrical device have a big impact on the device performance. This paper studies the impact of outflow inductance on the regulation of the output voltage of the device. The simulation study has been carried out in SIMULINK and also the results are presented.